Injonction comptable et révolution culturelle à l’Université - Frédéric Lebaron (La Nouvelle Revue du Travail)
The article uses the sociology of economics and public policy to examine financialisation-like processes occurring in the field of higher education and research. Although this sector is singular – if only because of the different ways in which it is monetarised – there is still evidence that belief processes (relating notably to economics’ driving role in today’s social order) have helped it to embrace a broader logic, one that might be construed as something that is partially, albeit not entirely, redolent of the logic characterising financial capitalism.